Recent advances in soft computing : proceedings of the 22nd International Conference on Soft Computing (MENDEL 2016) held in Brno, Czech Republic, at June 8-10, 2016 /: proceedings of the 22nd International Conference on Soft Computing (MENDEL 2016) held in Brno, Czech Republic, at June 8-10, 2016. (2017) - Unknown
No abstract available